The Factors Relating To Dietary Compliance on Sufferer of Diabetics Mellitus in Polyendocrine at Dr. Fauziah Hospital Bireun in 2018 - Vita Sari, Dian; Rosmalina (Akademi Keperawatan Kesdam Iskandar Muda Lhokseumawe, 2021)
Diabet mellitus (Desimeter) is a group of metabolic diseases that is characterized by hyperglycemia that occurs due to defects in insulin secretion, insulin action, or both. The purpose of the study was to determine the factors related to dietary compliance in patients with diabetes mellitus at the Endocrine Polyclinic of dr. Fauziah hospital Bireuen. This is descriptive method research using a cross sectional approach. The population in this study were all DM patients at the Endocrine Poly, dr. Fauziah Bireuen as many as 756 people and the number of samples taken were 32 people carried out by accidental sampling technique. The results obtained by the chi-square test showed some points that, firstly, participants aged 20-59 years old (95.0%) were more obedient to the DM's diet with a p-value of 0.000 and an OR = 2.01. The second, participant consists of males (88.9 %) who were more obedient to the DM's diet with a p-value of 0.003 and an OR=3.06. Third, participants with higher education (100%) were more obedient to the DM's diet with a p-value of 0.000. Fourth, participants who have good knowledge (81.0%) were more obedient to the DM's diet with a p-value of 0.020 and OR = 7.4, and respondents who have a good self-motivation (82.6%) were more obedient to the DM's diet with a p-value 0.003 and OR = 16.6. The last respondents who have good family support (81.8%) were more obedient to the DM's diet with a p-value of 0.013 and an OR value of 10.5. It is suggested for DM patients to be able to carry out and obey their diet therapy properly and correctly, in order to maintain the blood sugar levels are in the normal range. The Endocrine Polyclinic at Public Hospital dr. Fauziah Bireuen developed a program to increase the active participation of DM patients, especially type 2, in attending education or nutrition consultations.